A case study of a mother's intertwining experiences with incest and postpartum depression - Røseth, Idun (CoAction Publishing, 2011)
The association between childhood sexual abuse (CSA) and major depression disorder (MDD) gives reason to suspect that many mothers with postpartum depression (PPD) have a history of CSA. However, few studies have investigated how CSA and PPD are related. In this case study we explore how the experience of incest intertwines with the experience of postpartum depression. We focus on participant subject “Nina,” who has experienced both. We interviewed her three times and we analysed the interviews with Giorgi's phenomenological descriptive method to arrive at a contextualised meaning structure. Nina's intruding fantasies of men who abuse her children merge with her recollections of her own incest experiences. She may succeed in forcing these fantasies out of her consciousness, but they still alter her perceptions, thoughts, and emotions. She feels overwhelmed and succumbs to sadness, while she also is drawn towards information about CSA, which in turn feeds her fantasies. The psychodynamic concepts of repetition compulsion, transference, and projection may provide some explanation of Nina's actions, thoughts, and emotions through her past experiences. With our phenomenological stance, we aim to acknowledge Nina's descriptions of her everyday life here and now. With reference to Husserl, Heidegger, Merleau-Ponty, and Minkowski, we show that Nina's past is not a dated memory; rather it determines the structure of her consciousness that constitutes her past as her true present and future. Incest dominates Nina's world, and her possibilities for action are restricted by this perceived world. Any suspension of action implies anguish, and she resolves this by incest-structured action that in turn feeds and colours her expectations. Thus anxiety and depression are intertwined in the structure of this experience.